PREJUDICE IN AYMAN JAMAL’S BILAL: A NEW BREED OF HERO (2015) FILM - Ikrar Dyrata, Halwin Esa; Nasrullah, Nasrullah; Max, Jonathan Irene Sartika (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2021)
Prejudice is the common phenomena in our daily activity where people do not realize that they are prejudicing others. This often happens due to differences in the diversity that exist in society. People usually construct a stereotype for good or bad about individual or group. As a reflection of the real life, several films also contain the phenomenon of prejudice and one of them is Bilal: A New Breed of Hero. This research aims to analyze the prejudice contained in Bilal: A New Breed of Hero and also the characters struggle for freedom. This research was conducted by using a descriptive method and qualitative approach. In this research, researcher took data from the conversations of characters in the film. The results of this research show that there are fourteen data which are indicated as prejudice and four characterizations struggle aimed for freedom. In this study, there are five types of prejudice, namely antilocution, avoidance, discrimination, physical attack and extermination. The data obtained to examine character struggles only reached four of the five analyzes.